Contrast-Enhanced Ultrasound in the Differential Diagnosis of Primary Thyroid Lymphoma and Nodular Hashimoto’s Thyroiditis in a Background of Heterogeneous Parenchyma - Yang, Lulu; Zhao, Haina; He, Yushuang; Zhu, Xianglan; Yue, Can; Luo, Yan; Ma, Buyun (Frontiers in Oncology, 2021)
Objective: To investigate the diagnostic performance of contrast-enhanced ultrasound (CEUS) in the differentiation of primary thyroid lymphoma (PTL) and nodular Hashimoto thyroiditis (NHT) in patients with background of heterogeneous diffuse Hashimoto thyroiditis (HT). Methods : Sixty HT patients with 64 thyroid nodules (31 PTL and 33 NHT) who had undergone CEUS examination were included in this study. With histopathological results as the reference standard, we evaluated the imaging features of each nodule on both conventional ultrasonography (US) and CEUS. Quantitative CEUS parameters including peak intensity (PI), time to peak (TTP) and area under the time-intensity curve (AUC) were gathered in the nodule and background parenchyma. The ratio indexes of theses parameters were calculated by the ratio of the lesion and the corresponding thyroid parenchyma. Logistic regression and receiver operating characteristic (ROC) curves analyses of valuable US indicators were further preformed to evaluate the diagnostic capability of CEUS in discrimination of PTL and NHT. Results: Among all the observed US imaging features and CEUS parameters, ten indicators showed significant differences between PTL and NHT (all P<0.05). All the significant indicators were ranked according to the odds ratios (ORs). Eight of them were CEUS associated including imaging features of enhancement pattern, degree, homogeneity, and quantification parameters of PI, AUC, ratios of PI, AUC and TTP. While, indicators on conventional US, including vascularity and size ranked the last two with ORs less than 3. The five single CEUS parameters showed good diagnostic performance in diagnosis of PTL with areas under ROC curves of 0.72-0.83 and accuracies of 70.3%-75.0% . The combination of CEUS imaging features and the ratios of PI, AUC and TTP demonstrated excellent diagnostic efficiency and achieved area under ROC curve of 0.92, which was significantly higher than any of the five single parameters (all P<0.05) , with a sensitivity of 83.9%, specificity of 87.9% and accuracy of 85.9%. Conclusions: CEUS is an efficient diagnostic tool in the differential diagnosis of PTL and NHT for patients with diffuse HT. Conjoint analysis of CEUS imaging features and quantification parameters could improve the diagnostic values.